Synergistic coupling {101}-{111} facet of N-doped TiO2 film enhance spatial charge separation for methylene blue photodegradation - Hamed, N.K.A.; Nafarizal, N.; Ahmad, M.K.; Faridah, A.B.; Makhtar, S.N.N.M.; Noor, S.F.M.; Shimomura, M. (Elsevier, 2023)
The synthesis of N-doped TiO2 film with co-exposed {101} and {111} facets via a one-pot facile hydrothermal method had proven to enhance the photocatalytic activity of TiO2. The high-resolution transmission electron microscopy (HR-TEM) and X-ray photoelectron spectroscopy (XPS) data show the incorporation of N ions into the TiO2 accomplishes the facet modification. The shifting of the N-doped TiO2 photocatalyst adsorption bandgap toward a higher wavelength was identified as the TiO2 band gap was reduced. Up to 66 % methylene blue had successfully been degraded with the aid of N-doped TiO2 as an active photocatalyst. The enhanced photodegradation of N-doped TiO2 film is mainly attributed to the presence of {101} and {111} facets, leading to the efficient separation of carriers and lengthening the life of photogenerated carriers, consequently improving its photocatalysis potential.